Comparison of plain X-ray and MRI findings by determining the sensitivity and specificity in the diagnosis of lumbar spinal stenosis in rural population - Chougule, Soneshkumar R. (International Journal of Research in Medical Sciences, 2022)
Background: Lumbar spinal stenosis is the most frequent indication for spine surgery. The x-ray and MRI are the choice of investigation. Justified use of radiography can be cost effective in the management of lumbar spinal stenosis. Objective was to evaluate and compare the sensitivity and specificity of the plain x-ray and MRI in the diagnosis of the lumbar spinal stenosis. Methods: A multicenter cross sectional analytical study was carried out from July 2021 to August 2022 on 70 patients of both sexes aged more than 25 years with chronic low back pain. A descriptive analysis was performed for all data. Results: In the MRI, 35 (50.0%) cases had diskogenic spinal canal stenosis and 24 (34.3%) had both diskogenic and non diskogenic spinal canal stenosis. The validity of MRI evaluation for only diskogenic spinal canal stenosis was correlated, where the calculated values of plain x-ray were: sensitivity 80.0%, specificity 60.0%, accuracy 77.5%, positive predictive value 93.3% and negative predictive value 30.0%. The validity of MRI evaluation for both diskogenic and non diskogenic spinal canal stenosis was correlated, where the calculated values of plain x-ray were sensitivity 83.3%, specificity 66.7%, accuracy 80.0%, positive predictive value 90.9% and negative predictive value 50.0%. Conclusions: Plain x-ray is a useful and reliable diagnostic modality for the evaluation, assessment and the subsequent appropriate management of lumbar spinal stenosis.